2019
DOI: 10.1007/s10530-019-02055-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral VNIR-spectroscopy and imagery as a tool for monitoring herbicide damage in wilding conifers

Abstract: Wilding conifers, the naturally regenerated scions of exotic conifer species, are a major ecological and economic issue in New Zealand. Hyperspectral imagery could provide a useful means of monitoring the efficacy of wilding control measures but little research has examined this possibility. Data were collected from an experiment, that included thirty-nine young Pinus contorta (Douglas) trees allocated to a control and two herbicide treatments (triclopyr butoxyethyl ester and diquat dibromide monohydrate). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…The availability of P has an impact on many important aspects of photosynthesis (Marschner, 1995;Taiz et al, 2015) and, as shown in our study, P has been found to be significantly and positively related to both Vcmax and Jmax (Bown et al, 2007). Given that photosynthetic rate is also positively related to both PRI (Gamon et al, 2016;Ripullone et al, 2011;Scholten et al, 2019;Wong and Gamon, 2015a, b) and SIF (Frankenberg et al, 2011;Guanter et al, 2014;Smith et al, 2018) it follows that these traits were positively related to P when data was restricted to the P limiting range.…”
Section: Discussionsupporting
confidence: 82%
“…The availability of P has an impact on many important aspects of photosynthesis (Marschner, 1995;Taiz et al, 2015) and, as shown in our study, P has been found to be significantly and positively related to both Vcmax and Jmax (Bown et al, 2007). Given that photosynthetic rate is also positively related to both PRI (Gamon et al, 2016;Ripullone et al, 2011;Scholten et al, 2019;Wong and Gamon, 2015a, b) and SIF (Frankenberg et al, 2011;Guanter et al, 2014;Smith et al, 2018) it follows that these traits were positively related to P when data was restricted to the P limiting range.…”
Section: Discussionsupporting
confidence: 82%
“…Research has widely demonstrated the utility of PRI for predicting light use efficiency (Garbulsky et al 2011;Peñuelas et al 2011) and key photosynthetic parameters under a range of stresses including severe drought conditions (Ripullone et al 2011), cold winter temperatures (Gamon et al 2016;Wong and Gamon 2015a, b) and herbicide damage (Scholten et al 2019). The relationship found here between PRI and photosynthetic capacity is consistent with Scholten et al (2019) and has a strong theoretical basis as PRI can track plant photosynthetic activity through its intimate link with the dissipation of excess energy by nonphotochemical quenching (NPQ) via the xanthophyll cycle. The xanthophyll cycle is activated during periods of excess excitation energy in the leaf and through this process violaxanthin is de-epoxidized to zeaxanthin.…”
Section: Discussionmentioning
confidence: 99%
“…PRI provides a linkage with the efficiency of photosystem II through characterising variation in xanthophyll pigments and as such quantifies changes in non-photochemical quenching and light use efficiency (Gamon et al 1997). This index has been successfully used to predict photosynthetic rate (Drolet et al 2008;Fuentes et al 2006;Gamon et al 1997;Guo and Trotter 2004;Hilker et al 2008;Middleton et al 2009;Nichol et al 2000;Penuelas et al 1995;Stylinski et al 2000) and the photosynthetic response of plants subject to a range of stresses (Dobrowski et al 2005;Hernández-Clemente et al 2011;Scholten et al 2019;Suárez et al 2008) and is responsive to seasonal changes in pigments (Gitelson et al 2017). PRI can be readily used to scale photosynthesis to the canopy level as recently launched satellite based hyperspectral imagers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Applications in plant-based industries include fruit, grain and seed quality, particularly pathogen infestation and varietal purity, as well as chemical composition. The list of applications continues to grow rapidly [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%